The Antioxidant Activity and Acute Toxicity of Jamu Cekok: Kidney Histopathology Analysis of Female Wistar - Puji Astuti; Virhan Novianry (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Jamu cekok is a traditional Indonesian herbal remedy for toddlers to improve appetite. While previous studies have shown benefits such as weight gain, its antioxidant activity and safety profile remain underexplored. This study evaluated the antioxidant potential and acute toxicity of jamu cekok, composed of Curcuma xanthorrhiza, Curcuma longa, Zingiber officinale, and Kaempferia galanga. Extracts were extracted with Aquadest and n-hexane, and antioxidant activity was assessed via the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Results showed weak antioxidant activity in both extracts (IC50: 481.59 ppm for decoction, 127.12 ppm for n-hexane), lower than some individual herbs. Moreover, an acute toxicity tests followed OECD 425 guidelines using female Wistar rats. No mortality occurred at doses up to 5,000 mg/kgBW, categorizing it as practically non-toxic. However, elevated creatinine levels and histopathological kidney changes, including degeneration and Bowman’s capsule dilation, were observed at higher doses. These findings suggest jamu cekok is safe at high doses but may induce temporary renal effects. Further research is needed to optimize formulations and evaluate long-term safety.